Effects of in vitro fertilization and intracytoplasmic sperm injection treatment on female patients' perinatal mental health: systematic review and meta-analysis - Nemcova, Hana; Blaskova, Tereza; Horakova, Anna; Kuklova, Marie; Hrdlickova, Kristyna; Sebela, Antonin (Frontiers in Reproductive Health, 2025)
IntroductionIn vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) patients often experience stress, which exacerbates the burden associated with infertility and may lead to an increased risk of mental-health difficulties. In this systematic review and meta-analysis, we examined the effects of IVF or ICSI on female patients’ mental health.MethodsA database search was conducted in PubMed, Web of Science, and PsychInfo to select relevant studies. Forty-four studies involving 858,966 participants were included in the systematic review. The results of these studies were very heterogeneous and yielded contradictory findings. Two meta-analyses, comprising a total of seven studies, were conducted. The first calculated the standardized mean difference of symptoms of depression between women who became pregnant through IVF and those who conceived spontaneously. In the second, we compared symptoms of anxiety between these two groups.ResultsFive studies examined depressive symptoms and showed no significant difference between the two groups: SMD = −.15; 95% CI [−.33,.03], p = .10. A meta-analysis of six studies on anxiety symptoms revealed significantly higher levels in the IVF groups compared to the controls: SMD = .33; 95% CI [.17,.49], p < .001.DiscussionThe results suggest that the psychological effects of IVF/ICSI, especially with respect to anxiety, require attention and support from healthcare providers, although the effect size is small. Further studies with adequate sample sizes, including women with both successful and unsuccessful treatment, and adequately controlling for important confounders are needed to fully understand the effects of IVF/ICSI on mental health.Systematic Review RegistrationPROSPERO (CRD42023461472).